2005
DOI: 10.1002/anie.200501794
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Primer Extension: Efficiently Determining Single Nucleotides in DNA

Abstract: Rapid replication: Non‐enzymatic primer extension has previously been studied in the context of prebiotic chemistry, but not for practical applications. Reactions with primers featuring a 3′‐amino‐2′,3′‐dideoxynucleotide can be rapid and selective for all four templating nucleobases (see scheme). On a chip with immobilized capture strands, 500 fmol of template suffice for single‐nucleotide determinations within 2.7 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 28 publications
(22 reference statements)
1
73
1
Order By: Relevance
“…On the DNA template, the identity of the 5′ activated leaving group did not greatly affect absolute rates (within 5-fold; Table 2) and indeed affected the rates to a smaller degree than could have been expected based on assays comparing oxyazabenzotriazolides with 2-methylimidazolides. 24 For the RNA template, the imidazolides gave faster reactions than the OAt esters (by at most one order of magnitude). Stalling factors did not appear to be affected systematically by the identity of leaving group (Figure 2B; Supporting Figure S1B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the DNA template, the identity of the 5′ activated leaving group did not greatly affect absolute rates (within 5-fold; Table 2) and indeed affected the rates to a smaller degree than could have been expected based on assays comparing oxyazabenzotriazolides with 2-methylimidazolides. 24 For the RNA template, the imidazolides gave faster reactions than the OAt esters (by at most one order of magnitude). Stalling factors did not appear to be affected systematically by the identity of leaving group (Figure 2B; Supporting Figure S1B).…”
Section: Resultsmentioning
confidence: 99%
“…24 Mixing of equimolar quantities of the four OAt esters as previously described 19 gave solutions that were directly used for assays. Imidazolides of dNMPs were prepared via redox condensation using imidazole, 2,2′-dithiodipyridine and triphenylphosphine, as described for ribonucleotides by Lohrmann and Orgel.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was long considered that one major drawback of this type of polymerization was its error-proneness (close to 20% of misincorporation) [64], which would extremely reduce the applicability of this method for a nucleic acid of a length corresponding to known enzymatically-active RNA molecules. Irene Chen and co-workers [65,66] have however shown that the incorporation of a noncognate nucleobase at the 3′-end of a primer (terminated with 3′-NH 2 -ddNMP) reduces rates of a subsequent elongation by more than two orders of magnitude compared to those observed in the case of correct elongation.…”
Section: Rna Polymerization In Bulk Aqueous Mediamentioning
confidence: 99%